A Holistic Exploration of the Potentially Recoverable Redshift Information of Stage IV Galaxy Surveys - Bryan R. Scott; Alex I. Malz; Robert Sorba (The Astrophysical Journal)
Extragalactic science and cosmology with Stage IV galaxy surveys will rely almost exclusively on redshift measurements derived solely from photometry, which are subject to systematic and statistical uncertainties with numerous analysis choices. Single-survey photometric redshift estimates ought to be improved by combining data from multiple surveys, with common wisdom asserting that optical data benefits from additional infrared (IR) but not ultraviolet (UV) coverage. The degree of improvement for either is not well characterized, and attempts necessitate assumptions of a chosen estimator and its prior information. We apply an information-theoretic metric of potentially recoverable redshift information to assess the impact of multi-survey photometry without assuming an estimator or priors in the context of the Vera C. Rubin Observatory Legacy Survey of Space and Time ( lsst ) in the optical, Roman and Euclid ( roman and euclid ) in the IR, and Cosmological Advanced Survey Telescope for Optical-UV Research ( c astor ) in the UV. Our approach uses mock catalogs to approximate conditional relationships between color and redshift from real samples, but is otherwise independent of estimator and prior information. We conclude that adding UV photometry can benefit redshift determination of certain galaxy populations, but that gain is tempered by their decreased chance of meeting detection criteria at higher wavelengths. We explore the spectral energy distributions of galaxies whose potentially recoverable redshift information is most impacted by additional photometry. The holistic assessment approach we develop here is generic and may be applied to quantify the impact of combining photometric data sets, changing experimental design, optimizing observing strategy, and mitigating systematics.